AJAX Based Online Shopping Application - Zazali, Mardhia (Universiti Teknologi PETRONAS, 2008)
This document briefly explains the building of an e-commerce web application that implemented AJAX as defined for the latest available Web 2.0 technologies. It is a major intent of the project to introduce selected company and consumers an e-commerce web application that features increases in its interactivity, speed, functionality and usability. The web application is meant for the chosen SME Company to promote and make sales of their products through the internet more efficiently and effectively. Previously, customers for the company were people local to the company location. Deals were often handled face to face. Fortunately, this can be very much more improved by implementations taken by the project. Instead of only relying on sales made at their sales office, the products will be put onto display as for purchase on the new web application. Another important task of this project is also to improve the communications between seller and buyer. The seller or company contact details are provided at the web application. The project also worked on improving the methods of holding related business deals and transactions to be more efficiently done and secure. This is as well to expand their business into a much larger market hence increasing the opportunities of producing more profits and company size. This project is also motivated to change the users experience in browsing web applications. In the past few years and as it still is now, much of the internet applications rely on the server-client model. Other than the quality of existing web applications designs, the physical attributes of the networking local to each user distinguish one experience from another. The implementations made in this project overcome problems that may arise from that aspect. For example, people that had previously been unnecessarily put to wait just for their page reloads to appear can now have faster response from the web application. One of the major causes to this is the ability ofAJAX to make asynchronous calls to the web application server.